Strong hyperconjugative interactions limit solvent and substituent influence on conformational equilibrium: the case of cis-2-halocyclohexylamines - Francisco, Camila B.; Fernandes, Cleverton S.; de Melo, Ulisses Z.; Rittner, Roberto; Gauze, Gisele F.; Basso, Ernani A. (Beilstein Journal of Organic Chemistry, 2019)
The presence of strong stereoelectronic interactions involving the substituents in cis-2-substituted cyclohexanes may lead to results different from those expected. In this work, we studied the conformational behavior of cis-2-fluoro- (F), cis-2-chloro- (Cl), cis-2-bromo- (Br) and cis-2-iodocyclohexylamine (I) by dynamic NMR and theoretical calculations. The experimental data pointed to an equilibrium strongly shifted toward the ea conformer (equatorial amine group and axial halogen), with populations greater than 90% for F, Cl and Br in both dichloromethane-d2 and methanol-d4. Theoretical calculations (M06-2X/6-311++G(2df,2p)) were in agreement with the experimental, with no influence of the solvent or the halogen on the equilibrium. A principal component analysis of natural bond orbital energies pointed to the σ*C–X and σC–H orbitals and the halogen lone pairs (LPX) as the most significant for the hyperconjugative interactions that influenced the equilibrium. The σC–H → σ*C–X hyperconjugation and the interactions involving the LPX counterbalance each other, explaining the non-influence of the halogen on the conformational equilibrium. These interactions are responsible for the strong preference for the ea conformer in cis-2-halocyclohexylamines, being strong enough to restrain the shift in the equilibrium due to other factors such as steric repulsion or solvent effects.
Keywords: conformational equilibrium; cyclohexane derivatives; dynamic NMR; hyperconjugation; principal component analysis